2004
DOI: 10.1086/424927
|View full text |Cite
|
Sign up to set email alerts
|

Green Bank Telescope Observations of Interstellar Glycolaldehyde: Low-Temperature Sugar

Abstract: Interstellar glycolaldehyde (CH20HCHO) has been detected with the 100-m Green Bank Telescope (GBT) toward the star-forming region Sagittarius B2(N) by means of the 1~0 -1 0 1 , 2~1 -2~2 , 3~~-3 0~, and 413-404 rotational transitions at 13.48, 15.18, 17.98, and 22.14 GHz, respectively. An analysis of these four high signalto-noise rotational transitions yields a glycolaldehyde state temperature of ~8 K. Previously reported emission line detections of glycolaldehyde with the NRAO 12-m telescope at mm-wavelengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
142
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(158 citation statements)
references
References 12 publications
13
142
2
1
Order By: Relevance
“…Dashed lines show LSR velocities of +64, +73, and +82 km s À1 . Molecules with no hyperfine ( HF ) structure previously observed with the GBT such as propenal (CH 2 CHCHO), propanal (CH 3 CH 2 CHO), and glycolaldehyde (CH 2 OHCHO) show absorption components at +64 and +82 km s À1 and an emission component at +73 km s À1 ( Hollis et al 2004a( Hollis et al , 2004b. In general, the cyanide spectra shown in the left panels of Figure 1 are consistent with this source velocity structure.…”
Section: Speciessupporting
confidence: 78%
See 1 more Smart Citation
“…Dashed lines show LSR velocities of +64, +73, and +82 km s À1 . Molecules with no hyperfine ( HF ) structure previously observed with the GBT such as propenal (CH 2 CHCHO), propanal (CH 3 CH 2 CHO), and glycolaldehyde (CH 2 OHCHO) show absorption components at +64 and +82 km s À1 and an emission component at +73 km s À1 ( Hollis et al 2004a( Hollis et al , 2004b. In general, the cyanide spectra shown in the left panels of Figure 1 are consistent with this source velocity structure.…”
Section: Speciessupporting
confidence: 78%
“…This suggests that the reactions were driven more by the radiation dose than the sample temperature (Hudson & Moore Note.-The chemical bonding energies were obtained at the MP2/ aug-cc-pVTZ level of theory (Frisch et al 2004;Dunning 1989;Kendall et al 1992;Woon & Dunning 1993 (Chengalur & Kanekar 2003). Such shocks have been presumed to be responsible for the formation and distribution of large aldehyde molecules toward this region (Hollis et al 2004a(Hollis et al , 2004b. Furthermore, it is also well known that there is ambient UV flux and cosmic-ray flux in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous spectral surveys (see, e.g., Turner 1989;Schilke et al 2001;Belloche et al 2009;Herbst & van Dishoeck 2009;Tercero et al 2010) have revealed that hot molecular cores are characterized by a large abundance of simple organic molecules, including H 2 CO (formaldehyde), HCOOH (formic acid), and complex organic molecules (COMs, organics containing ≥6 atoms), such as CH 3 OH (methanol), HCOOCH 3 (methyl formate), and CH 3 OCH 3 (dimethyl ether). Although some larger COMs have low abundances in hot molecular cores, e.g., CH 3 CH 2 OH (ethanol; Rizzo et al 2001), CH 3 COCH 3 (acetone; Snyder et al 2002), CH 3 CHO (acetaldehyde; Nummelin et al 2000), (CH 2 OH) 2 (ethylene glycol; Hollis et al 2002), and CH 2 OHCHO (glycolaldehyde; Hollis et al 2000Hollis et al , 2004, they have been previously detected towards the Galacticcentre hot molecular core source SgrB2 (N-LMH). Because of their high degree of chemical and structural complexity, the precise origins and formation mechanisms of these COMs is still a subject of debate.…”
Section: Introductionmentioning
confidence: 99%
“…48,15.18,17.98,and 22.14 GHz,respectively;all solely in emission; all the other transitions were seen predominantly in absorption. An analysis of these four rotational transitions yields a glycolaldehyde state temperature of ∼8 K (Hollis et al 2004a) that is probably characteristic of the cold halo region surrounding the LMH. Other large molecules that have been detected predominantly in absorption toward Sgr B2(N-LMH) with the GBT by means of transitions between low-energy levels include propenal (CH 2 CHCHO; Hollis et al 2004b), propanal (CH 3 CH 2 CHO; Hollis et al 2004b), acetamide (CH 3 CONH 2 ; Hollis et al 2006a), and cyclopropenone (c-H 2 C 3 O; Hollis et al 2006b).…”
mentioning
confidence: 99%